MODEL OPTIMASI PENGELOLAAN SAMPAH DI TPA - Adi Darmawan; Tri Edhi Budhi Soesilo; Sri Wahyono (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2020)
The increase in waste generation is a major problem especially for urban areas such as Jakarta with insufficient landfill capacity and an inefficient and environmentally sound waste management system. To produce an optimal, integrated and sustainable landfill management strategy, an analysis of the TPST Bantargebang waste management system is then formulated towards optimization of sustainable landfill management in environmental, financial, and social aspects through a system dynamics intervention scenario model of the TPST Bantargebang waste management system. Based on the descriptive analysis carried out on the latest waste management, 3 main issues are known, namely, landfill capacity almost fully occupied, methane gas emissions increment, and the possibility waste pickers integration to increase scavenging productivity. Simulations were carried out with a system dynamics model for the 2018-2023 period with BAU conditions and an intervention scenario with a reduction in landfill waste and a reduction in waste flow. The results of the scenario are: landfill can still be utilized until 2023; methane gas emissions decreased by an average of 23,50%; the increase in the Scavenger Production Ratio to the Landfill Waste Rate reached 134,58%. As a consequence of the intervention and the addition of waste treatment activities in the TPST Bantargebang, the operational cost per ton has increased up to 309,62%. This study concludes that the scenario of incoming waste reduction and existing landfill waste reduction planned by Material Recovery Facility (MRF) construction with scavenger involvement, compost processing efficiency improvement, construction of Waste to Energy (WtE) facilities in the form of incinerator, landfill mining, and reprofiling simultaneously.